The influence of packaging design elements upon consumer buying behaviour among young adults towards food products - Ngoi, Zhong Sheng; Lee, Odelia (2020)
In recent years, competitive in food industry is getting intense. This caused manufactures have to put more effort to increase their food packaging’s communication capacity and quality, so that consumer especially young adults could approach to them. Therefore, this project “The Influence of Packaging Design Elements Upon Consumer Buying Behaviour Among Young Adults Towards Food Products” is aim to find out the perception of young adults towards the packaging design for food products, to examine whether the packaging elements will affect the young adults' buying decision and to identify the importance of packaging elements toward buying decisions. We chose consumer decision-making process model as our theory due to this theory suits with our research study and could help researchers and viewers to understand more about consumer buying behaviour. Other than this, qualitative research method was chosen as it is considered to have a naturalistic approach in an unrestrained setting, one with which tries to comprehend a certain phenomenon; therefore, it is more suitable in analysing and collecting the appropriate data for this research. Besides, this research utilized phenomenology as it attempts to unravel the emotions an individual feel, attitudes, perceptions and experiences. Moreover, observation and focus group interview are chosen to collect the data. The participants of 5 people for observation and 10 people for focus group interview with ages of 18 to 24 years was determined. In addition, Kampar has been picked as the research conduct and collect data location.